2021
DOI: 10.3389/fmed.2021.637241
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Chronological Changes in Serum Triglycerides Are Associated With the Time Point for Non-alcoholic Fatty Liver Disease Development in the Nationwide Korean Population Cohort

Abstract: Background: We investigated the effects of anthropometric, laboratory, and lifestyle factors on the development of non-alcoholic fatty liver disease (NAFLD) in a nationwide, population-based, 4-year retrospective cohort.Methods: The propensity score-matched study and control groups contained 1,474 subjects who had data in the Korean National Health Insurance Service-National Sample Cohort in 2009, 2011, and 2013. NAFLD was defined using medical records of a diagnosis confirmed by primary clinicians and meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A Japanese study included 27,064 nonobese and non-NAFLD subjects, and found that the risk of NAFLD increased by 60% when weight increased by 3 kg [ 34 ]. Rim, et al studied the relationship between the changes in various indices and the incidence of NAFLD and they found that TG decreases by 9.46 mg/dl in men and 5.98 mg/dl in women as well as a weight increase by 0.36 kg were associated with an increased incidence of NAFLD [ 35 ]. However, these studies did not analyze potential differences in risk by age group.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study included 27,064 nonobese and non-NAFLD subjects, and found that the risk of NAFLD increased by 60% when weight increased by 3 kg [ 34 ]. Rim, et al studied the relationship between the changes in various indices and the incidence of NAFLD and they found that TG decreases by 9.46 mg/dl in men and 5.98 mg/dl in women as well as a weight increase by 0.36 kg were associated with an increased incidence of NAFLD [ 35 ]. However, these studies did not analyze potential differences in risk by age group.…”
Section: Discussionmentioning
confidence: 99%